Dampak Terjadinya Kekerasan Fisik Oleh Guru Terhadap Anak di Lingkungan Sekolah - Sabriyanti Tanaiyo; Moh. R.U. Puluhulawa; Nuvazria Achir (Lembaga Pengembangan Kinerja Dosen, 2024)
The problems that occur in the world of education do not only revolve around the socio-economic sector, but have also penetrated the legal realm, as can be seen from the many cases that have arisen in the school environment related to violence perpetrated by unscrupulous teachers against their students. Teachers who should be at the forefront in fortifying and protecting children at school actually do the opposite. The problem raised in this research is: what is the impact of physical violence by teachers on children in the school environment. This research is directed at empirical legal research and the approach used in this research uses a statutory regulation approach and a case approach. This research was carried out at Gorontalo Police. The results of the research and discussion explain that the impacts felt by students as a result of physical violence committed by teachers are divided into 3 (three), namely physical, psychological and social impacts.